2019
DOI: 10.1002/pat.4574
|View full text |Cite
|
Sign up to set email alerts
|

Study of effective parameters on wear behavior of rubbers based on statistical methods

Abstract: This study investigates the wear, surface roughness, and temperature buildup (TBU) of styrene butadiene rubber (SBR), natural rubber (NR), and nitrile butadiene rubber (NBR) while sliding over abrasives of different sizes with the variation of normal load. Rubber properties such as tensile strength (s) and elongation at break (e) were considered as input parameters. Individual, as well as interacting effects of different parameters, were analyzed in‐depth by using statistical methods. Overall wear of rubber de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, there is a clear difference in the variation of the The wear amount of the SS304 seal pairs under different loads is shown in Figure 7. Some studies have shown that an increase in pressure leads to an increase in metal wear [25], and the two curves showed similar trends. The total amount of mass loss was almost the same at the end of the tests.…”
Section: Time-variable Characteristics Of Mass Loss Of Fkm/ss304 Pairsmentioning
confidence: 70%
“…However, there is a clear difference in the variation of the The wear amount of the SS304 seal pairs under different loads is shown in Figure 7. Some studies have shown that an increase in pressure leads to an increase in metal wear [25], and the two curves showed similar trends. The total amount of mass loss was almost the same at the end of the tests.…”
Section: Time-variable Characteristics Of Mass Loss Of Fkm/ss304 Pairsmentioning
confidence: 70%
“…This decrease in COF was also due to the conversion of friction into the heat energy, in addition to providing the required energy for tearing and partial melting of the coating. In addition, the temperature rose due to friction, as reported, reducing the friction coefficient associated with lubricous chromium oxide layer formation [ 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hakami et al investigated the wear, surface roughness, and temperature increase of styrene-butadiene rubber, natural rubber, and nitrile-butadiene rubber when shifted over abrasive materials of various sizes, with normal load variation. The properties of rubber, such as tensile strength and elongation at break were regarded as input parameters [19]. In another paper, Hakami et al investigate rubber wear rate and mechanisms and the related affecting parameters based on the data published in the literature.…”
Section: Conveyor Belt Specimensmentioning
confidence: 99%